Залишковий час обслуговування в системі GI/G/1/∞ - Братійчук, M.С. (Видавничий дім "Академперіодика" НАН України, 2008)
For a GI/G/1/∞-type queueing system, the remaining service time at time t is under consideration. Its distribution as t → ∞ is considered as well.